2019
DOI: 10.1039/c9nr02870f
|View full text |Cite
|
Sign up to set email alerts
|

High strength nanostructured films based on well-preserved β-chitin nanofibrils

Abstract: Chitin nanofibrils (ChNFs) are interesting high-value constituents for nanomaterials due to the enormous amount of waste from the seafood industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 61 publications
5
52
0
Order By: Relevance
“…Again in table 1, we include the composite matrix of the regenerated chitin films/nanopapers that have much smaller Young's modulus, which vary between 6 and 9 GPa [71][72][73][74][75]. Wu et al [72] and Montroni et al [77] explored the excessive chemical treatment and indeed reported 15% decrease in their mechanical performance. If the fibrillar structure of the chitin is used in its native form using mechanical fibrillation techniques, chitin fibrils can offer a number of excellent properties such as an axial fibril modulus of around 60 GPa One of the key factors for conservation of mechanical properties is keeping the hydrogen bonding between the chitin acetyl groups during such treatments.…”
Section: Mechanical Properties Of Chitinmentioning
confidence: 99%
See 1 more Smart Citation
“…Again in table 1, we include the composite matrix of the regenerated chitin films/nanopapers that have much smaller Young's modulus, which vary between 6 and 9 GPa [71][72][73][74][75]. Wu et al [72] and Montroni et al [77] explored the excessive chemical treatment and indeed reported 15% decrease in their mechanical performance. If the fibrillar structure of the chitin is used in its native form using mechanical fibrillation techniques, chitin fibrils can offer a number of excellent properties such as an axial fibril modulus of around 60 GPa One of the key factors for conservation of mechanical properties is keeping the hydrogen bonding between the chitin acetyl groups during such treatments.…”
Section: Mechanical Properties Of Chitinmentioning
confidence: 99%
“…All of these processes disrupt the hierarchical structure of the exoskeleton and cause a drastic loss in mechanical properties [3]. Again in table 1, we include the composite matrix of the regenerated chitin films/nanopapers that have much smaller Young's modulus, which vary between 6 and 9 GPa [71][72][73][74][75]. Wu et al [72] and Montroni et al [77] explored the excessive chemical treatment and indeed reported 15% decrease in their mechanical performance.…”
Section: Mechanical Properties Of Chitinmentioning
confidence: 99%
“…In these previous works, the fiber cross-sectional width was near half (3-9 nm) that obtained in the present work, and it is known that thinner and larger nanofibers show higher mechanical properties. In general, the mechanical properties of NF films are influenced by chitin chemical composition (e.g., Mw, CI, DA) and nanofiber structure (length/width ratio), which in turn depends on the biopolymer source along with the isolation procedure, and the NF preparation methods [43,49,50]. Other properties that could affect the nanofibrillated chitin film mechanical properties are the porosity, protein content, thickness, preparation method, and NF orientation [51][52][53].…”
Section: Mechanical Colorimetric and Swelling Degree Propertiesmentioning
confidence: 99%
“…[91,92] More detailed information on the overall top-down nanofibrillation process is available elsewhere. [84,93] Creating nanopapers in bottom-up fashion, on the other hand, obviates the need for a high-energy apparatus by taking advantage of supramolecular self-assembly of NFs from a solution. Several solvent systems (e.g., aqueous alkali/urea, [94,95] halide/ organic solvent, [96] ionic liquids, [97] etc.)…”
Section: Materials and Nanofibrillation For Nfrps And Nanopapersmentioning
confidence: 99%